Exercise heart rates in patients with hypertrophic cardiomyopathy - Luo, Hong-Chang (2015)
The exercise heart rate (HR) profile and its relation to cardiac function and arrhythmias were investigated in patients with hypertrophic cardiomyopathy (HC). Chronotropic response (CR) and heart rate recovery (HRR) were computed during and after treadmill exercise testing in 273 patients with HC and 95 age-matched healthy controls. Patients with HC had higher prevalence of chronotropic incompetence and lower HRR1-5min compared with controls. Exercise capacity, diastolic function (assessed by E/e') and left atrial volume index were associated with HRR1min and CR in HC. Septal myectomy was associated with reduction in chronotropic incompetence but did not affect HRR1min. In conclusion, impaired CR and HRR1min are associated with advanced disease and do not appear to be independent clinical markers indicating high-risk status in HC. Improving CR by titrating doses of negative chronotropic agents, myectomy, and atrial pacing may be useful to increase exercise capacity in patients with HC.